COMMERCIAL STRATEGIES FOR THE TOURIST DEVELOPMENT OF ORCHID GARDENS IN THE CARCHI PROVINCE - Carvajal Pérez, Luis Alfredo; Salas Valencia, Rosario Maribel (Tierra Infinita, 2021)
The development of this research seeks to determine the profile of the client who visits the orchid gardens of the Carchi province to establish marketing strategies. Through a qualitative and quantitative analysis of the tourist profile of the clients, it was possible to establish the marketing strategies that can be implemented in orchid gardens to promote tourism growth in the province. In addition, a greater presence of the Ecuadorian tourism market segments from Ibarra and tourists from Colombia was identified. In conclusion, it is highlighted that orchid gardens want to position themselves in the tourist market, while seeking the conservation and protection of orchid species, while they are more rare or difficult to find, they will also have a high value.
Keywords: orchid gardens; tourist demand; commercial strategies; tourism growth